Ecological and mechanical assessment of lightweight fiber-reinforced concrete made with rubber or expanded clay aggregates. (30th November 2016) - Fantilli, Alessandro P.; Chiaia, Bernardino; Gorino, Andrea
Highlights: Rubber granulates is used herein to cast an eco-friendly lightweight concrete (RLC). RLC is compared with a traditional lightweight concrete with expanded clay (TLC). The results of the eco-mechanical analyses depend on the chosen functional unit. When compressive strength is the functional unit, TLC shows the best performances. Referring to a structural parameter, the use of RLC plates is more convenient. Abstract: To reduce the environmental impact of traditional lightweight concrete (TLC), porous aggregates can be substituted by rubber granulates. The mechanical properties of such rubber lightweight concrete (RLC) are investigated and compared with those of TLC made with expanded clay aggregates. Uniaxial compression and three point bending tests were performed for assessing the mechanical and ecological performances of the two mixtures, containing or not plastic fibers. As a result, when compressive strength is the functional unit of the analyses, TLC performs better than RLC. Conversely, fiber-reinforced RLC is the best solution when flexural strength and structural ductility are the required performances.